Matrix preconditioning techniques and applications - Chen, Ke, 1962- (Cambridge monographs on applied and computational mathematics, 2005)
Very much a users-guide, this book provides insight to the use of preconditioning techniques in areas such as acoustic wave scattering, image restoration and bifurcation problems from electrical power stations. Supporting MATLAB files are available via the Web to assist and develop readers' understanding, and provide stimulus for further study.